Systellaspis debilis ... - D'Acoz, Cédric D'Udekem; Degrave, Sammy (Zenodo, 2018)
Systellaspis debilis (A. Milne-Edwards, 1888) A near-cosmopolitan pelagic species recorded from the Australian Antarctic sector (Iwasaki & Nemoto 1987a). Iwasaki & Nemoto (1987a) stated that Balss (1925) recorded it from the Indian Antarctic Sector, but this is an error. ... : Published as part of D'Acoz, Cédric D'Udekem & Degrave, Sammy, 2018, A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps, pp. 201-240 in Zootaxa 4392 (2) on page 218, DOI: 10.11646/zootaxa.4392.2.1, http://zenodo.org/record/1195302 ...